Immune-related adverse events following checkpoint inhibitor treatment in head and neck cancers: A comprehensive review - Remi Kessler; Subramanya Pandruvada (Oral Oncology Reports)
Head and neck cancers are a heterogeneous group of highly aggressive tumors and collectively represent the sixth most common cancer worldwide. Most head and neck cancers are squamous cell carcinomas (HNSCCs). Immunotherapy agents, namely anti-PD-1/PD-L1 and CTLA-4 inhibitors, are the cornerstone of treatment for recurrent/metastatic HNSCC. Immune-related adverse events (irAEs) of varying severity are a known phenomenon associated with administering such agents to patients. Currently, there is no elucidating literature on the incidence, types, and treatment of irAEs in HNSCC and how managing such events impacts the temporary or permanent discontinuation of a particular immunotherapeutic agent. In this comprehensive literature review conducted through PubMed, we sought to analyze all available research on irAEs in HNSCC. Our initial search results were in 34 articles, 33 of which ultimately met the criteria for inclusion. Of those 33, four were systematic reviews/meta-analyses, four were retrospective reviews, and nine were case reports. A synthesis of the available research underscored the dearth of information available on which patients may be at greater risk for irAEs and why certain agents may not be successful in specific patient populations. The results of our study highlight the need for future clinical trials to be focused on immune-related adverse events and how they impact the overall management of patients with recurrent/metastatic HNSCC.